2013
DOI: 10.1111/1753-6405.12084
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Gaps: competing estimates of Indigenous Australian life expectancy in the scientific literature

Abstract: Objective: Closing the gap in life expectancy between Indigenous and other Australians within a generation is central to national Indigenous reform policy (Closing the Gap). Over time, various methods of estimating Indigenous life expectancy and with that, the life expectancy gap, have been adopted with differing, albeit non-comparable results. We present data on the extent of the gap and elucidate the pattern of use and interpretations of the different estimates of the gap, between 2007 and 2012.Methods: An e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 58 publications
(114 reference statements)
0
15
0
Order By: Relevance
“…The estimates of the IBOD, however, differed from those previously used. Prior to the IBOD study, the variance was often cited as 17 years, and this figure was central to the advocacy campaign leading to the government's official commitment to CTG …”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The estimates of the IBOD, however, differed from those previously used. Prior to the IBOD study, the variance was often cited as 17 years, and this figure was central to the advocacy campaign leading to the government's official commitment to CTG …”
Section: Findings and Discussionmentioning
confidence: 99%
“…Prior to the IBOD study, the variance was often cited as 17 years, and this figure was central to the advocacy campaign leading to the government's official commitment to CTG. 20,34,35 The availability of Kenneth Hill, a highly respected demographer, to the IBOD research team offered the possibility of recalculating the life expectancy gap using Generalized Growth Balance indirect methods, 36 complementing the IBOD study, but not integral to it. The IBOD estimate of the gap-about 13 years-was much smaller than the accepted ABS estimate, although the difference was a product of the new methodologies and not a basis for comparison.…”
Section: Life Expectancymentioning
confidence: 99%
See 1 more Smart Citation
“…This particular paper draws on data collected from a literature review, a systematic review, and key informant interviews, to elucidate the story behind the IBoD study – why it was commissioned, the context in which this occurred, and the expectations of the different stakeholders involved. It complements our study on the measurement and presentation of the life expectancy gap in Indigenous health [ 24 ] and will sit alongside related papers examining the process and findings of the IBoD study.…”
Section: Methodsmentioning
confidence: 86%
“…However, this relationship was not significant in students between the ages of 16 and 18; and the results of this research are in line with those of the present research, which states that there is a significant relationship between social intelligence and adaptability. In addition, Snyder (2007) showed that high levels of hope in university students is a predictor of higher scores, better chances for graduation, and lower likelihood of failure (26). In addition, he indicated that BA graduates with higher scores of hope have better adaptability skills and choose better strategies for their education stages.…”
Section: Discussionmentioning
confidence: 99%